2002
DOI: 10.2754/avb200271020159
|View full text |Cite
|
Sign up to set email alerts
|

Functional Morphology of Adrenergic Innervation of Guinea Pig Spleen

Abstract: Innervation of the spleen in guinea-pigs was studied. Adrenergic nerve components of the organ were visualized by glyoxylic acid histofluorescence method. The adrenergic nerve components enter the spleen in a common bundle with arteries. In the organ first they form characteristic dense periarterial plexiform arrangements of thicker and thinner nerve profiles, which are especially conspicuous around the aa. centrales running through the white pulp. Then, nerve fibres extend away from these plexuses into the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
1
3
1
Order By: Relevance
“…Our findings of the AChE-positive nerve fibres in the red pulp are in contrast with described data of some authors (2,11) found in the rat and rabbit spleen but are in agreement with the presence of adrenergic nerve fibres in the guinea-pig spleen (14). The occurence of the AChE-positive nerve fibres in the red pulp of the guinea-pig spleen is probably associated with the presence of contractile elements (8).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our findings of the AChE-positive nerve fibres in the red pulp are in contrast with described data of some authors (2,11) found in the rat and rabbit spleen but are in agreement with the presence of adrenergic nerve fibres in the guinea-pig spleen (14). The occurence of the AChE-positive nerve fibres in the red pulp of the guinea-pig spleen is probably associated with the presence of contractile elements (8).…”
Section: Discussionsupporting
confidence: 83%
“…We did not find any AChE-positive nerve fibres in the guinea-pig splenic capsule but Elfvin et al (5) and Siroťáková et al (14) observed in this animal a dense network of immunoreactive and catecholaminergic nerve fibres in the splenic capsule, as well as, in the subcapsular compartment.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…In the regulation of vascular motility of the spleen, adrenergic nerve components play an important role Siroťáková et al 1999Siroťáková et al , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…BuChE-positive innervation of the spleen in rats is marked by the more common characteristics with the adrenergic supply of this organ in other small mammals (5,6,19) and BuChE-positive innervation in rabbits (20) and concerning the fact that these nerves enter the organ together with arteries round which they form very conspicuous and typical thicker nerve plexiform formation that fulfil the role of a carrying substrates for the peripheral neuro-effector actions.…”
Section: Discussionmentioning
confidence: 96%